EU‐wide Economic and Environmental Impacts of CAP Greening with High Spatial and Farm‐type Detail. (19th May 2017) - Gocht, Alexander; Ciaian, Pavel; Bielza, Maria; Terres, Jean‐Michel; Röder, Norbert; Himics, Mihaly; Salputra, Guna
Abstract: In this paper we analyse the economic and environmental impacts of CAP greening introduced by the 2013 CAP reform using the CAPRI model. CAPRI captures the farm heterogeneity across the EU and it allows to depict the implementation of the greening measures in high detail while integrating the environmental effects and the market feedback of the simulated policy changes. The simulated results reveal that the economic impacts (land use, production, price and income) of CAP greening are rather small, although some farm types, crops (fallow land and pulses) and Member States may be affected more significantly. The CAP greening will lead simultaneously to a small increase in prices and a small decrease in production. Farm income slightly increases because the price effects offset the production decline. Similarly to economic effects, the environmental impacts (GHG emissions, N surplus, ammonia emissions, soil erosion, and biodiversity‐friendly farming practices) of CAP greening are small, although some regions may see greater effects than others. In general, the environmental effects at EU level are positive on a per hectare basis, but the increase in UAA can reverse the sign for total impacts. Overall, simulated GHG and ammonia emissions decrease in the EU, while the total N surplus, soil erosion and biodiversity‐friendly farming practices indicator slightly increase due to the CAP greening.